Chiles and smoke : BBQ, grilling, and other fire-friendly recipes with spice and flavor - Prose, Brad (Harvard Common Press, 2023)
"In Chiles and Smoke, pitmaster and professional recipe developer Brad Prose turns up the heat for smoky and savory barbecued meats, seafood, and vegetables"--